FREE RADICAL SCAVENGING AND ANTIOXIDANT POTENTIAL ACTIVITY OF CASSAVA PLANTS - Javad Mehran, Mohammad; Zendehbad, Hossein; Malla, Sudhakar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Abstract: To isolate and quantify the protein and reducing sugar content of the cassava roots together with the antioxidant potential assays, which also included the inhibitory values on free radicals. The cassava roots were pulverized and extracted with both aqueous and organic extraction phases. The total protein content and reducing sugars and the flavonoid contents were estimated as per the protocol for all the four extract fractions. In addition, the free radical scavenging activity and SOD assay was done on all the four extracts. The total polyphenol content and the antioxidant potential assay was also estimated and to correlate the positive relation between the polyphenol content and the antioxidant power. The aqueous extract showed more content of reducing sugars and total protein content and flavonoids. The free radical scavenging activity was also more for the aqueous extract. In contrary the SOD activity was more towards the hexane fraction than the other three extraction phases. There is also positive correlation observed between the polyphenol content and the antioxidant power of the extracts. The cassava, a staple food though lacks the vitamin C content and is responsible for malnutrition among the consumers, it still has a good load of antioxidants which can make the plant a natural protective towards stress related diseases. Â  Key words: Cassava, DPPH, SOD, Antioxidant potential activity.